Minimum-time B-spline trajectories with corridor constraints. Application to cinematographic quadrotor flight plans. (August 2019) - Rousseau, Gauthier; Stoica Maniu, Cristina; Tebbani, Sihem; Babel, Mathieu; Martin, Nicolas
Abstract: This paper proposes a novel strategy for completing a flight plan with a quadrotor UAV, in the context of aerial video making. The flight plan includes different types of waypoints to join, while respecting flight corridors and bounds on the derivatives of the position of the quadrotor. To this aim, non-uniform clamped B-splines are used to parameterize the trajectory. The latter is computed in order to minimize its overall duration, while ensuring the validation of the waypoints, satisfying the flight corridors and respecting the maximum magnitude on its derivatives. A receding waypoint horizon is used in order to split the optimization problem into smaller ones, which reduces the computation load when generating pieces of trajectories. The effectiveness of the proposed trajectory generation technique is demonstrated by simulation and through an outdoor flight experiment on a quadrotor.